Comparison of Abbott LCx Chlamydia trachomatis Assay With Gen-Probe PACE2 and Culture. Issue 2 (2000) - Young, David C.; Craft, Sandra; Day, Mary-Clare; Davis, Barbara; Hartwell, Elizabeth; Tong, Song
Abstract : In this study the LCx assay (a nucleic acid amplification assay) for Chlamydia trachomatis in endocervical samples was compared with the Gen-Probe PACE2 assay (a nucleic acid probe assay) for endocervical samples, and with endocervical culture. In addition, the efficacy of the LCx assay was determined for midstream clean-catch urine samples because it is often necessary to obtain such a sample for routine urine culture and it is simpler to collect only a single sample without also collecting a first-void urine for LCx. Endocervical specimens from 205 patients were tested for C. trachomatis via LCx and PACE2. Of these patients, 203 were tested by culture. Midstream cleancatch urine samples from 75 of these patients were tested by LCx. The sensitivities and specificities for these assays, after discrepant analysis, were 100 and 98.9% for LCx of endocervical samples, 52.4 and 100% for PACE2; and 71.4 and 100% for culture. The sensitivity/specificity of LCx for midstream clean-catch urines was 66.7/98.5%. The apparent prevalence of C. trachomatis in our population was 10.2%. These data indicate that among the methods tested, LCx of endocervical samples had the highest sensitivity for C. trachomatis in this population. The senstivity of the urine LCx assay using midstream clean-catch collected urines was considerably less than that reported in other studies that used first-void urines but was higher than that of PACE2. Infect. Dis. Obstet. Gynecol. 8:112–115, 2000.